The decline in average family size and its implications for the average benefits of within-household sharing - Carsten Schröder; Katrin Rehdanz; Daiju Narita; Toshihiro Okubo (Oxford Economic Papers, 2015)
Economic policies rely on demographic projections. Yet in making these projections, researchers often ignore the aspect of household formation—despite sustained trends in many industrialized countries towards smaller household units with fewer members. Over the long term, this trend is likely to reduce the benefits of sharing goods/services within households (household economies of scale) at the micro-level, thereby increasing household-sector demand at the macro level. We propose a framework to (a) quantify the level of household economies of scale for different household types and (b) assess how the decline in average household size impacts aggregate household-sector demand. We apply the framework to energy consumption in Japan. The application indicates that household economies of scale in energy use are substantial and that the 5% decline in average household size in Japan between 2005 and 2010 led to an economy-wide loss in household economies of scale amounting to almost 4%.
Additional information: This is a pre-copyedited, author-produced PDF of an article accepted for publication in Oxford Economic Papers following peer review. The version of record "The Decline in Average Family Size and Its Implications for the Average Benefits of Within-Household Sharing / Carsten Schröder, Katrin Rehdanz, Daiju Narita, Toshihiro Okubo. In: Oxford Economic Papers 67 (2015), 3, pp. 760-780" is available online at: http://dx.doi.org/10.1093/oep/gpv033
Keywords: D11; J10; Q42; D12; 330